Antibacterial Activity of Ethanol, Ethyl Acetate, and n-Hexane Extracts of Bidara Laut Lignum (Strychnos lucida R.Br) against Staphylococcus aureus and Escherichia coli - Setyaningsih, Erwi Putri; Bahri, Saiful; Nurjanah, Rindang (Tropical Biopharmaca Research Center, IPB University, 2024)
Strychnos lucida is empirically believed to have efficacy in treating various diseases such as fever, malaria, toothache, and stomachache and to treat wounds. The secondary metabolite of Strychnos lucida has various polarity. The purpose of this study was to compare the inhibitory activity of Strychnos lucida extracts against E. coli and S. aureus bacteria. The test was carried out by measuring the Diameter of the Inhibitory Region (DIR) using the disc diffusion method on a concentration of 90%, 75%, 60%, 45%, 30%, and 15%. The Minimum Inhibitory Concentration (MIC) was carried out by agar dilution method on a concentration of 15%, 12.5%, 10%, 7.5%, 5%, and 2.5%. The positive control was 1% ampicillin, and the negative control was 10% DMSO. The ethyl acetate extract showed the highest DIR of 14.30 mm against S. aureus and E. coli on a concentration of 45%, ethanol extract was 8,38 mm against S. aureus and 8.71 mm against E. coli, and n-hexane had no inhibitory activity on a concentration 45%. The result of the MIC test for ethanol and ethyl acetate extract for both bacteria was found at a concentration of 15%, while n-hexane extract against Staphylococcus aureus was found at a concentration of 90% and a concentration of 75% against Escherichia coli.